ChemInform Abstract: New Orally Effective 3‐(2‐Nitro)phenylpropanamide Analgesic Derivatives: Synthesis and Antinociceptive Evaluation. Issue 13 (1st April 2014) - Since, Marc; Freret, Thomas; Nee, Gerald; Terme, Thierry; Vanelle, Patrice; Boulouard, Michel
Abstract A variety of 3‐(2‐nitro)phenylpropanamide derivatives (III) (20 examples) are synthesized and screened for their peripheral analgesic activities on acetic acid‐induced writhing in mice.